2021
DOI: 10.3390/cancers13040872
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Analysis Reveals CCR5 as a Key Target for CRISPR Gene Editing to Regulate In Vivo NK Cell Trafficking

Abstract: A growing number of natural killer (NK) cell-based immunotherapy trials utilize ex vivo expansion to grow and activate allogenic and autologous NK cells prior to administration to patients with malignancies. Recent data in both murine and macaque models have shown that adoptively infused ex vivo expanded NK cells have extensive trafficking into liver tissue, with relatively low levels of homing to other sites where tumors often reside, such as the bone marrow or lymph nodes. Here, we evaluated gene and surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…A detailed transcriptomic analysis demonstrated ex vivo expanded NK cells had drastic differences in expression pattern of chemotactic receptors and ligands, including a significant downregulation of CXCR4 and consequent upregulation of CCR5. The study further observed knocking out CCR5 resulted in reduced NK cell trafficking into liver and corresponding increase in NK cell presence in the blood circulation in immunodeficient mice post-infusion (105). PB-NK cells transfected with CCR7 had increased towards CCL19, a lymph node-associated chemokine (112).…”
Section: Effects Of Other Cytokines and Chemokines On Nk Cell Expansi...mentioning
confidence: 78%
See 1 more Smart Citation
“…A detailed transcriptomic analysis demonstrated ex vivo expanded NK cells had drastic differences in expression pattern of chemotactic receptors and ligands, including a significant downregulation of CXCR4 and consequent upregulation of CCR5. The study further observed knocking out CCR5 resulted in reduced NK cell trafficking into liver and corresponding increase in NK cell presence in the blood circulation in immunodeficient mice post-infusion (105). PB-NK cells transfected with CCR7 had increased towards CCL19, a lymph node-associated chemokine (112).…”
Section: Effects Of Other Cytokines and Chemokines On Nk Cell Expansi...mentioning
confidence: 78%
“…Efficient tumor infiltration and homing of NK cells is vital for effective anti-tumor activity. However, cells within the TME secrete chemokines such as C-X-C motif chemokine ligand 8 (CXCL8) or C-C motif chemokine ligand 2 (CCL2) that suppress the activity of intratumoral NK cells (105). High concentrations of adenosine in primary and metastatic TME, specifically myeloid cell adenosine A2A receptors (A2ARs) have a myelosuppressive effect that leads to suppression of NK cell anti-tumor activity (106).…”
Section: Effects Of Other Cytokines and Chemokines On Nk Cell Expansi...mentioning
confidence: 99%
“…It is possible that the cells did transit to the bone marrow, but did not persist long enough to be detected at the time of sacrifice or to eliminate AML cells from the bone marrow. Results from others indicate that homing of expanded NK cells into the bone marrow may be inhibited due to increased C-C chemokine receptor type 5 (CCR5) expression and decreased C-X-C chemokine receptor type 4 (CXCR4) expression [ 30 ]. The same group showed improved bone marrow homing of NK cells in NSG mice via transfection with CXCR4 R334X , a gain-of-function variant [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“… 99 Knocking out CCR5 from expanded NK cells (using CRISPR/Cas9 technology) reduces trafficking into liver tissue but increases the number of NK cells in the circulation and lung following adoptive transfer into immunodeficient mice. 100 Human Eomes hi NK cells show high liver residency, whereas circulating Eomes low NK cells can upregulate Eomes expression if stimulated by cytokines such as IL-15 and transforming growth factor-β (TGF-β) released during inflammation. Upregulated Eomes is believed to increase the expression of CCR5 on NK cells.…”
Section: Nk Cell Trafficking and Homing At Steady Statementioning
confidence: 99%